A study on factors towards affecting house pricing among employees and customers of Matrix Concepts Holdings Berhad / Nur Dalilah Mahashim - Mahashim, Nur Dalilah (2015)
The purpose of this study is to determine the factors towards affecting house pricing among employees and customers of Matrix Concepts Holdings Berhad. For this study only 100 of respondents which are employees and customers at Matrix Concepts Holdings Berhad were selected using simple random sampling. The objectives of this study aim to identify the factors that influence and contribute the factors towards affecting house pricing among employees and customers at Matrix Concepts Holdings Berhad and to ascertain the best predictor to affect factors towards affecting house pricing among employees and customers at Matrix Concepts Holdings Berhad. Besides that, this study is a quantitative research study whereby the findings of the study were analyzed by using the Statistical Package for the Social Sciences (SPSS). The data collected in this study is analyzed by using frequency, descriptive analysis, reliability, Pearson’s correlation analysis and multiple regressions in order to achieved the research objectives. Eventually, this study discovered that most of the respondents were male, Malay, single and most of them have a scale of household monthly income range between RM1500 and below. In addition, multiple regressions also answered the research objective one where cost of constructions, housing criteria and government policy become the factor that contribute factors towards affecting house pricing since its P value is less than 0.05. In order to answer the second research objective, cost of constructions which has the highest t-value became the best predictor to influence factors towards affecting house pricing among employees and customers of Matrix Concepts Holdings Berhad.